The Implementation of Project-Based Learning in English Class Academic Year 2019/2020 Mulawarman University - Deny Ramadani; Effendi Limbong; Ida Wardani (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2021)
This study focused on the PBL implementation in English teaching for students at English department. The purposes of this study were: (1) to know how Project based-learning (PBL) is implemented in English teaching; (2) to know the problems faced by the lecturer during the implementation of Project based-learning method in English teaching.This research was a type of descriptive research, and the approach used is qualitative research. The research subject was an English lecturer from English Department Mulawarman University. The data collection techniques were observation sheet note and interview. The data were classified according to the identified problems and were analyzed by using descriptive analysis method. The result of this study showed that the lecturer implemented PBL which was relevant with step by step by expert, Lecturer have known it since she were in high school, but she are not sure if the method used by high school lecturers is Project Based Learning. As for the result of the second research question, technological problems (i.e: unstable connection, delay, display error) and pedagogical problems (i.e: time consuming in preparing a lesson plan, need to provide a lot of stimulation media, and unable to conduct collaborative work) occurred during PBL implementation. Based on the findings of the study, it was concluded that the lecturer used step by step according to the expert but the arrangement is diferent baucause it adapts to the situation in the classroom, and the lecturer used six PBL procedures, (1) stimulation (2) problem statement (3) data collection (4) data processing (5) verification (6) generalization in her English teaching although, during its implementation, she faced technological and pedagogical problems. It was suggested for the lecturer to keep practicing in using PBL in the teaching process, be more patient in creating creative activities, and discuss the lesson plan with other English lecturers. Meanwhile, for the next researcher, it is suggested to explore the use of PBL in other skills or in courses that use not too much theory such as microteaching courses and other courses, since the current study only focused on the implementation of PBL in English phonology course.